Pengaruh Profitabilitas, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Sektor Goods Consumer Non-Cyclical Periode 2019-2023 - Syfa Hayatina; Laila Wardani (Postgraduate, University of Mataram, 2025)
This research aims to analyze the effect of profitability, capital structure and company size on company value with dividend policy as a moderating variable. This research is a causal associative research with a quantitative approach. In this research, sample selection was carried out using a purposive sampling method which focused on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2019-2023 research period. By considering the established criteria, the sample was obtained from 25 companies from 125 companies so that the research data analyzed amounted to 125 observations. In this research, the panel data regression model is applied using the Fixed Effect Model (FEM) approach, while testing the moderating variables is carried out using Moderated Regression Analysis (MRA). The model data analysis utilizes the Eviews version 12 program. The research show that profitability has a significant positive effect on company value. Capital structure has insignificant but unidirectional (positive) effect on company value. Company size has insignificant and unidirectional (negative) effect on company value. Dividend policy is able to moderate by strengthening the effect of profitability on company value. Dividend policy is able to moderate by weakening the effect of capital structure on company value. Dividend policy is unable to moderate the effect of company size on company value.